Calcium signaling in endocardial and epicardial ventricular myocytes from streptozotocin‐induced diabetic rats. Issue 4 (30th November 2020) - Al Kury, Lina T; Sydorenko, Vadym; Smail, Manal MA; Qureshi, Muhammad A; Shmygol, Anatoly; Papandreou, Dimitrios; Singh, Jaipaul; Howarth, Frank Christopher
Abstract: Aims/Introduction: Abnormalities in Ca 2+ signaling have a key role in hemodynamic dysfunction in diabetic heart. The purpose of this study was to explore the effects of streptozotocin (STZ)‐induced diabetes on Ca 2+ signaling in epicardial (EPI) and endocardial (ENDO) cells of the left ventricle after 5–6 months of STZ injection. Materials and Methods: Whole‐cell patch clamp was used to measure the L‐type Ca 2+ channel (LTCC) and Na + /Ca 2+ exchanger currents. Fluorescence photometry techniques were used to measure intracellular free Ca 2+ concentration. Results: Although the LTCC current was not significantly altered, the amplitude of Ca 2+ transients increased significantly in EPI‐STZ and ENDO‐STZ compared with controls. Time to peak LTCC current, time to peak Ca 2+ transient, time to half decay of LTCC current and time to half decay of Ca 2+ transients were not significantly changed in EPI‐STZ and ENDO‐STZ myocytes compared with controls. The Na + /Ca 2+ exchanger current was significantly smaller in EPI‐STZ and in ENDO‐STZ compared with controls. Conclusions: STZ‐induced diabetes resulted in an increase in amplitude of Ca 2+ transients in EPI and ENDO myocytes that was independent of the LTCC current. Such an effect can be attributed, at least in part, to the dysfunction of the Na + /Ca 2+ exchanger. Additional studies are warranted to improve our understanding of the regional impact of diabetes on Ca 2+ signaling, which will facilitate the discovery of new targeted treatments for diabetic cardiomyopathy. Abstract : This is the first report to investigate the effects of streptozotocin‐induced diabetes on L‐type Ca 2+ current simultaneously measured with Ca 2+ transients in epicardial and endocardial left ventricular myocytes isolated from rats 5–6 months after the induction of diabetes. Streptozotocin‐induced diabetes causes a progressive increase in the amplitude of endocardial and epicardial myocyte Ca 2+ transients that is independent of the L‐type Ca 2+ current. The effect of streptozotocin‐induced diabetes on Ca 2+ handling might be attributed, at least in part, to the dysfunction of the Na+/Ca 2+ exchanger.